THE MODERATING ROLE OF BOARD GENDER DIVERSITY ON THE RELATIONSHIP OF ENVIRONMENTAL, SOCIAL AND GOVERNANCE, CAPITAL INTENSITY TO TAX AVOIDANCE - Mukhtaruddin, Mukhtaruddin; Fuadah, Luk Luk; Asngari, Imam; Novriansa, Agil; Kalsum, Umi; Siahaan, Hani (JRAK, 2026)
This research explores corporate tax avoidance (TA) by assessing the roles of capital intensity (CI) and environmental, social, and governance (ESG) performance, while also considering board gender diversity (BGD) as a moderating factor within non-financial firms in ASEAN. The study is based on panel data from 185 companies observed over a five-year timeframe. The empirical evidence demonstrates that ESG engagement is significantly associated with variations in tax avoidance behavior, indicating that firms with stronger ESG commitments tend to adopt distinct tax strategies. Capital intensity is also identified as a key determinant, showing a stable and statistically significant relationship across all estimation models. To enhance analytical rigor, firm-level characteristics such as profitability (ROA), leverage (DER), and company size (FS) are included as control variables. Moreover, the findings reveal that board gender diversity strengthens the interaction between capital intensity and tax avoidance, highlighting the importance of governance structure in shaping corporate tax decisions. The study further observes a notable rise in tax avoidance activities among ASEAN firms during the COVID-19 period, both in immediate and extended horizons. These results underline the urgency for regulators to implement more robust ESG disclosure standards to improve transparency and ensure more effective tax supervision.